2009
DOI: 10.1063/1.3200956
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of size effects in Pb(Zr0.54Ti0.46)O3 thin film capacitors with platinum and LaNiO3 conducting oxide electrodes

Abstract: The problem of thickness dependence of dielectric and ferroelectric properties of Pb͑Zr 0.54 Ti 0.46 ͒O 3 ͑PZT͒ thin film capacitors is addressed. Experimental data collected on PZT capacitors with different thicknesses and different electrode configurations, using platinum and LaNiO 3 conducting oxide, are examined within the prism of existing models. Available literature data, abounding but contradictory, led us to conclude that in the range of thickness investigated, size effect under all its aspects, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Due to its versatility, rf-sputtering method was proposed even for mass production of PZT films [19][20][21]. Although multiple studies reported the preparation and ferroelectric properties of PZT films [22,23], for device applications, it is still needed to understand the role of composition and microstructural parameters (crystallite orientation, grain size, stoichiometry, interfaces) on the macroscopic properties and the possibility to control the microstructures by the deposition parameters and the nature and orientation of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its versatility, rf-sputtering method was proposed even for mass production of PZT films [19][20][21]. Although multiple studies reported the preparation and ferroelectric properties of PZT films [22,23], for device applications, it is still needed to understand the role of composition and microstructural parameters (crystallite orientation, grain size, stoichiometry, interfaces) on the macroscopic properties and the possibility to control the microstructures by the deposition parameters and the nature and orientation of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…7,32,33 In a recent article, investigation of PZT capacitors, the same as those studied in the present paper, led the authors to identify the depolarization field ͑E dep ͒ inherent to interface chemistry as being the vector of the different facets of size effect. 24 Deterioration of r and P r , increasing E c as well as elongation of hysteresis loop accompanying thickness downscaling were indeed explained by considering existence at the interfaces of small nonferroelectric regions with low permittivity. Moreover, presence in these regions of charged defects, mainly located at the upper Pt-film interface, was a necessary condition in explaining why in some cases E c was affected by thickness downscaling but not P r .…”
Section: Discussionmentioning
confidence: 95%
“…In previous investigations devoted to size effects, we apply this criterion on fresh samples of different thicknesses. 24,34 This procedure, achieved by adjusting the amplitude of the applied voltage, amounts to restore a similar inner polarization loop, close to saturation, in the bulk ferroelectric layer of each sample. In fine this simply returns to compensate for the voltage drop across the interface capacitance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations